2018
DOI: 10.3892/mmr.2018.9442
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane‑induced neurotoxicity is driven by OXR1 post‑transcriptional downregulation involving hsa‑miR‑302e

Abstract: Sevoflurane is a common anesthetic agent used in surgical settings and previous studies have indicated that it exerts a neurotoxic effect. However, the molecular mechanism underlying this side effect is unknown. In addition, the human microRNA‑302 (hsa‑miR‑302) family members have been reported to be involved in neuronal cell development and biology. Thus, the present study aimed to investigate the potential implication of hsa‑miR‑302e in the sevoflurane‑induced cytotoxicity on human hippocampal cells (HN‑h). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
0
18
1
Order By: Relevance
“…It participates in the detoxification of ROS and exhibits an important role in protecting various human cells against oxidative damage (Li et al, 2014;Svistunova et al, 2019). Different from previous reports that OXR1 expression was suppressed under stress (Ingram et al, 2007;Yang et al, 2018), OXR1 showed upregulation upon H 2 O 2 exposure in the present study. Then, pre-treatment with 6S effectively reversed the upregulation of OXR1 in a dose-dependent manner (Figure 2), indicating that OXR1 might play important roles in the protective effects of 6S against apoptosis.…”
Section: S Inhibited the Expression Of Oxr1 In Ratcontrasting
confidence: 88%
“…It participates in the detoxification of ROS and exhibits an important role in protecting various human cells against oxidative damage (Li et al, 2014;Svistunova et al, 2019). Different from previous reports that OXR1 expression was suppressed under stress (Ingram et al, 2007;Yang et al, 2018), OXR1 showed upregulation upon H 2 O 2 exposure in the present study. Then, pre-treatment with 6S effectively reversed the upregulation of OXR1 in a dose-dependent manner (Figure 2), indicating that OXR1 might play important roles in the protective effects of 6S against apoptosis.…”
Section: S Inhibited the Expression Of Oxr1 In Ratcontrasting
confidence: 88%
“…Sevoflurane treatment increases levels of oxidative damage and cell death. However, experimentally increasing OXR1 levels abolished the ROS-associated toxicity of sevoflurane (Yang et al, 2018). Piperlongumine functions by a completely different mechanism.…”
Section: Depletion Of Oxr1 Affects Neurodegeneration and Cell Deathmentioning
confidence: 93%
“…Primer sequences were as follows: U6 forward primer (FP), 5′-GTGCTCGCTTCGGCAGCACATATAC-3′, reverse primer (RP), 5′-AAAAATATGGAACGCTTCACGAATTTG-3; GAPDH FP, 5′-ACCCACTCCTCCACCTTTGA-3′, RP, 5′-CTGTTGCTGTAGCCAAATTCGT-3′; hsa-miR-424 FP, 5′-CGCAAAACGTGAGGCGCT-3′ -3′, RP, 5-CCAGTGCAGGGTCCGAGGTA-3′; TLR4 FP, 5′-AATGGATCAAGGACCAGAGG-3′, RP, 5′-CAGCCAGCAAGAAGCATCAG-3′. The PCR program consisted of 30 s at 95 °C, followed by 45 cycles of 5 s at 95 °C and 58 °C for 34 s. The expression level of miRNA was obtained using the 2 − ∆∆Cq method with U6 small nuclear RNA as control, and GAPDH as internal control for TLR4 [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured at 37 °C in 95% humidity and 5% CO2. 6 different treatments which cell underwent are as follows: sevoflurane (Sev), negative control oligonucleotide (NC), miR-424 mimic (mimic), pLenti-GIII-CMV vector (pcDNA), and pLenti-GIII-TLR4 plasmid (TLR4) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%